CORAK NEO-SUFISMEULAMA TAREKAT SYATARIYAH: STUDI JARINGAN ULAMA NUSANTARA ABAD KE-17 - Faslah, Roni (JURNAL AT-TURAS, 2016)
The ulama in Archipelago had great contributions to the Islamic studies and sciences. In addition to the Islamic branches, such as hadith, tafsir, and fiqh, there is an important subject of the 17th science, i.e. tasawwuf. It consists of emergence of the sufi orders in Archipelago, including Syattariah which is firstly built by Abdurrauf al-Sinkili with his teachers Al-Qusyasi and Al-Kurani at Haramain (Mecca and Medina). Al-Sinkili is a central figure in his efforts of developing the 17th sufi order in Archipelago. This article attempts to make a chronological map of neo-sufism which became a symbol of integration of the syariah and tasawuf. Furthermore, the development of Sunni orthodoxy is a typical characteristic of social religious landscape friendly with local culture in Archipelago.